AESTHETIC VERSUS FUNCTIONAL SEQUELAE: THE PSYCHOLOGICAL IMPACT ON YOUTH WITH CLEFT LIP MEASURED AGAINST A SEEMINGLY NON-COMPARABLE CONDITION - Diana Lora Parvu; Mario Zama; Oana-Maria Udrea; Catalin Ion Chiriac-Babei; Raluca Teodora Tatar; Diana Monica Preda; Adrian Vicentiu Voiculescu; Alexandru Ulici; Dan Mircea Enescu (Romanian Journal of Oral Rehabilitation)
Introduction The perceived psychological effect of facial scarring can be debilitating to a patient, especially to someone at a vulnerable age, so much so as a physical disability. The study seeks to provide valuable insights into just how that powerful that effect is, proving that the perceived quality of life of patients living with aesthetic cleft lip sequelae, namely functional scoliosis sequelae is comparable. Methods We developed an original 20 question survey, with established acceptable psychometric properties, addressing three major concern areas: social skills and integration, emotional repercussions and feelings, self-esteem and perception. The survey was applied to a unilateral cleft lip study group and a moderate to severe scoliosis one, both groups consisting of 30 patients aged 15-24 who underwent successful corrective surgery. Results The outcomes disclosed the fact that participants had indistinguishable fears, concerns and limitations, regardless of their underlying purely aesthetic or functional condition, thus providing a better apprehension on the psychology behind their behavior. Having similar answers in all three addressed areas, according to the Two-One Sided Equivalence Test (TOST) used for the statistic analysis, there were no significant differences between the two study groups. Provided the already exposed state of mind of apparently healthy teenagers, the study results should be interpreted concordantly with the socio-affective development particularities of this age group, taking into considerations potential limitations in generalizing these results. Conclusions The difficulties in experiencing a normal, proactive day to day life without emotional impairment was utterly noticeable in cleft lip participants, in spite of the limited patient number. Therefore, the desideratum is to comprehend the perceived psychological effect of facial sequelae in order to obtain better clinical communication, better understanding of their overall satisfaction and therefore diminished need for elective surgical procedures.